2011
DOI: 10.1142/s0129054111008908
|View full text |Cite
|
Sign up to set email alerts
|

On the Average State Complexity of Partial Derivative Automata: An Analytic Combinatorics Approach

Abstract: The partial derivative automaton ([Formula: see text]) is usually smaller than other nondeterministic finite automata constructed from a regular expression, and it can be seen as a quotient of the Glushkov automaton ([Formula: see text]). By estimating the number of regular expressions that have ε as a partial derivative, we compute a lower bound of the average number of mergings of states in [Formula: see text] and describe its asymptotic behaviour. This depends on the alphabet size, k, and for growing k's it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…By Proposition 3, |α R | Σ = |α| Σ and by the fact that ε ∈ π(α) if and only if ε ∈ ← − π (α), the analysis of the average size of A pd (α) presented in Broda et al [2] carries on to ← − A pd (α). Thus the average sizes of A pd and ← − A pd are asymptotically the same.…”
Section: Average-case Complexitymentioning
confidence: 98%
“…By Proposition 3, |α R | Σ = |α| Σ and by the fact that ε ∈ π(α) if and only if ε ∈ ← − π (α), the analysis of the average size of A pd (α) presented in Broda et al [2] carries on to ← − A pd (α). Thus the average sizes of A pd and ← − A pd are asymptotically the same.…”
Section: Average-case Complexitymentioning
confidence: 98%
“…In this section we compute and study the cost generating functions E k (z) and T k (z), and their asymptotic behaviours. The other functions used herein, as well as details on how to obtain them, can be found in the above cited article and in Broda et al [BMMR11b]. A more detailed description of the below computations can be found in a companion technical report of this paper [BMMR11a].…”
Section: Counting the Number Of Transitions In The Glushkov Automatonmentioning
confidence: 99%
“…Broda et al [BMMR11b] gave a lower bound of the number of mergings of states in π(α) with respect to Pos(α), which allowed to obtain an upper bound on the average state complexity of A pd (α). There, it was observed that the merging of states is primarily caused by sub-expressions γ of α such that ε ∈ π(γ).…”
Section: Counting the Mergings Of Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From RE to NFA a standard algorithm is the partial derivative automaton construction (A pd ) introduced by Antimirov [1], which coincides with the resolution of systems of equations by Mirkin [20]. The average complexity of these conversions was recently studied using the framework of analytic combinatorics [4,5], and also their extension to regular expressions with shuffle [7]. For these studies, Mirkin's construction is essential as it provides inductive definitions that can be used to obtain generating functions.…”
Section: Introductionmentioning
confidence: 99%